The Musical Nationalism: a Look from Two Representative Works for Symphonic Band by Latin American Composers - Meza Solano, Juan Carlos (2021)
Nationalism in music, conceived as the search for the identity of a particular culture through the use of folkloric elements, is a trend that has had an impact on the music composed for symphonic band during the XX and XXI century. The possibilities that this movement offers to the composers are very rich and varied, allowing them new forms of expression with very particular resources. At the same time, this has made musicians and directors study and learn certain musical features from different regions, in order to get as close as possible to what the composers wished to express. Thus, the practice of using nationalistic elements in Latin American works for symphonic band has been approached in this study regarding the interpretation of two representative works: Suite 200 (2010), by Colombian composer Victoriano Valencia (1970); Preludio and Scherzo (2009) by Costa Rican Vinicio Meza (1968).